An optimisation model for the design of energy efficient discrete event controllers. (1st January 2013) - Ng, Tsan Sheng; Nguyen, Francis Ngoc Hoang Long
In this work, we propose a mixed integer programming model that can be applied to design the rule base matrix of a discrete event controller (DEC) in order to optimise energy consumption of the resources while adhering to meet budget and completion time constraints. The model is solved using a hybrid linear programming and genetic algorithm (GA) approach and the obtained optimised schedule is transformed into matrices as inputs to the supervisory controller DEC. The proposed methodology is implemented on an assembly project and yields encouraging results in generating a good quality schedule within an acceptable time. It is also evident that the proposed method arrives at optimal solution with better completion time as compared to MIP method.